The Effect of Vetiver Roots on Stability Slope - Siagian, Agung Prasetya; Yelvi; Praditya, Andikanoza (Jurnal Poli-Teknologi, 2024)
Slope stability is a crucial factor in land management, especially in the context of environmental protection and erosion control. Vetiver plants can increase the compressive and shear strength of soil. The purpose of this research is to analyze the effect of vetiver roots on soil cohesion and shear angle in the laboratory and to analyze the effect of vetiver roots on slope stability using Geostudio Slope/w software in 2024. The analysis method used is the bishop method. The results obtained based on laboratory testing state that vetiver roots that have an age of 5-6 months increase the cohesion value from 0.099 kg/cm2 to 0.240 kg/cm2. The cohesion value increased by 142% at a depth of 20 cm against a slope of 35.54°. Based on the slope stability analysis using Geostudio slope/w in 2024, the largest percentage increase in safety factor (SF) value was obtained at 4.98% with a distance between vetiver plants of 80 cm and 10.32% with a distance between vetiver plants of 30 cm. However, the subsequent increase in root length did not affect the safety factor (SF) value.